Akh, Lev Ivanych, Lev Ivanych… . Akh, Lev Ivanych, Lev Ivanych… . Oh, Lev Ivanych, Lev Ivanych… . Ах, Лев Иваныч, Лев Иваныч… - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The documentary is devoted to the Soviet football player Lev IAshin. Contributors: Zababurin, V. (Director) Документальный фильм о советском футболисте Льве Яшине. Создатели: Забабурин, В. (Режиссер)